New Feminism in China Young Middle-Class Chinese Women in Shanghai - Zheng, Jiaran; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2016)
Based on rich empirical data and findings concerning the lives, perceptions and ambitions of young middle-class women graduates, this book provides insight into the lives and perceptions of a previously un-researched group in China from a feminist scholarly perspective. This study shows how the lives of young women and debates over youthful femininity lie at the very heart of modern Chinese history and society. With the central focus of women$1 (Bs issues, the ultimate concerns for this book is for facilitating Western readers to better understand the changing ideologies and the overall social domain of China under the leadership of President Xi. The empirical data displayed in this book include interviews, group discussions and additionally, illustrations, tables and other forms of images collected during a prolonged period of fieldwork. The insights presented in this book contribute to the cross-cultural communication with both Western feminist academics and readers who are sensible to different cultures.s
Feminism In China -- Third-Wave Feminism In The West -- A Feminist Research In China -- New Feminism In China.
Keywords: Social sciences; Sociology; Sex (Psychology).; Gender expression; Gender identity; Social Sciences; Gender Studies; Electronic books